Pengaruh Perencanaan Pajak, Penghindaran Pajak, dan Likuiditas Terhadap Nilai Perusahaan dengan Transparansi Perusahaan Sebagai Variabel Moderasi (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2019-2023) - Eva Ria Susanti Br Purba; Azwansyah Habibie; Syamsul Bahri Arifin (Journal of Innovative and Creativity, 2025)
This study examines and analyzes the effect of three independent variables, Tax Planning, Tax Avoidance, and Liquidity, on Firm Value, with Corporate Transparency as a moderating variable. The population of this study consists of manufacturing companies in the consumer good industry sector listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sampling technique used was purposive sampling, resulting in a total sample of 28 companies. The data were obtained from company financial statements and analyzed using SPSS version 26. The result of this study indicates that tax planning has no significant effect on firm value, while tax avoidance and liquidity have a significant impact on firm value. Corporate transparency can moderate the relationship between tax planning and tax avoidance on firm value; however, it does not moderate the relationship between liquidity and firm value.